2005
DOI: 10.1191/0969733005ne826oa
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Islam and Traditional Practices on Women’s Health and Reproduction

Abstract: The aim of this study was to investigate the effects of Islam as a religion and culture on Turkish women's health. The study included 138 household members residing in the territory of three primary health care centers in Turkey: Güzelbahçe, Fahrettin Altay and Esentepe. Data were collected by means of a questionnaire prepared by a multidisciplinary team that included specialists from the departments of public health, psychiatric nursing and sociology. We found that the women's health behavior changed from tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 2 publications
(2 reference statements)
2
16
0
5
Order By: Relevance
“…In this sense, lower IQ groups may be more susceptible to the potentially deleterious health effects conferred by adherence to strong religious orthodoxy (e.g., reduced access to reproductive health education and care, particularly among women), whereas high IQ groups may be more flexible in their thinking and decision making regarding social issues. This hypothesis seems consistent with a recent finding that, among Islamic women, women's health behavior changed from traditional to rational as education levels increased (Bahar et al, 2005). Thus, an interactive (i.e., joint) effect of IQ and religiosity on health outcomes is expected, especially those concerning reproductive issues.…”
Section: Current Studysupporting
confidence: 83%
See 1 more Smart Citation
“…In this sense, lower IQ groups may be more susceptible to the potentially deleterious health effects conferred by adherence to strong religious orthodoxy (e.g., reduced access to reproductive health education and care, particularly among women), whereas high IQ groups may be more flexible in their thinking and decision making regarding social issues. This hypothesis seems consistent with a recent finding that, among Islamic women, women's health behavior changed from traditional to rational as education levels increased (Bahar et al, 2005). Thus, an interactive (i.e., joint) effect of IQ and religiosity on health outcomes is expected, especially those concerning reproductive issues.…”
Section: Current Studysupporting
confidence: 83%
“…In addition, they noted that in traditional Arab society, exposure of the body is perceived as a violation of modesty and may arouse feelings of discomfort and embarrassment, thus decreasing the likelihood that women seek, or have access to, health care. Similar results regarding the influence of religion on practices related to pregnancy, abortion and family planning were found among Islamic Turkish women (Bahar et al, 2005). In particular, these authors found that women's health behavior changed from traditional (i.e., based on religious doctrine) to rational (i.e., based on medical science) as education levels increased.…”
Section: Religiosity-heath Associationssupporting
confidence: 51%
“…However, numerous health researchers have cautioned that the presumed positive impact of religion is either unwarranted (e.g., Sloan, Bagiella, & Powell, 1999) or at least premature (Powell, Shahabi, & Thoresen, 2003). Indeed, Reeve (2009) reviewed several studies which show negative effects of religiosity on health and health care utilization, particularly with respect to women's health issues (e.g., Azaiza & Cohen, 2006;Bahar et al, 2005;Gyimah, Takyi, & Addai, 2006).…”
Section: Religiosity-health Associationsmentioning
confidence: 94%
“…The effects of Islam and traditional practices on Turkish women's reproductive health have been described, with God seen as the ''ultimate healer'' (Bahar et al, 2005). A woman said when she was in labor, ''I have ritual ablution, pray to God, [and] worship God when I leave home to go to the hospital'' (p. 559).…”
Section: Review Of the Literaturementioning
confidence: 99%